In situ synthesis of carbon @ diatomite nanocomposite adsorbent and its enhanced adsorption capability. (4th July 2017) - Sun, Zhiming; Yao, Guangyuan; Xue, Yanlei; Sun, Wen; Zheng, Shuilin
ABSTRACT: Carbon @ diatomite (C@DE) nanocomposite was synthesized using glucose as precursor and purified diatomite as carrier through a facile hydrothermal carbonization process. The microstructure and interface properties of the obtained nanocomposites were characterized by SEM, TEM, FTIR, XPS and zeta potential analyzer. A batch adsorption study showed that the adsorption process was very fast and the kinetic data well fitted with pseudo-second-order kinetic model. Compared to pure carbon materials, the C@DE nanocomposite exhibits higher adsorption ability for Cr (VI). This kind of nanocomposite is a promising candidate as an adsorbent for the removal of Cr (VI) ions from wastewater.